Mindfulness for musicians: A mixed methods study investigating the effects of 8-week mindfulness courses on music students at a leading conservatoire. (June 2022) - Czajkowski, Anne-Marie L.; Greasley, Alinka E.; Allis, Michael
Mindfulness courses are beneficial in clinical domains for anxiety and depression and are becoming more prevalent as interventions in education. However, little is known about what effects mindfulness might have on musicians. In an exploratory study, 25 music students, who completed one of four 8-week MBSR/MBCT mindfulness courses adapted for musicians at the Guildhall School of Music and Drama, completed the validated Five Facet Mindfulness Questionnaire and a bespoke Mindfulness for Musicians questionnaire pre- and post-intervention. Twenty-one music students also took part in a post-intervention one-to-one semi-structured interview. Post-intervention mindfulness scores for both questionnaires increased significantly in comparison to pre-intervention scores. In interviews, participants were reportedly more aware and focused in instrumental lessons, were less self-critical, and developed increased body awareness, which improved their learning of instrumental technique. Participants also described enhanced teacher/pupil communication. In instrumental practice sessions, participants reported more efficient, effective and creative practice, and said that mindfulness exercises helped them deal with problems experienced while practising. Participants also described enhanced listening skills and improved socio-collaboration in ensemble rehearsals. They reported that mindfulness strategies had positive effects on music performance anxiety and described changes in time perception, enhanced expressivity, and positive post-performance effects. Future researchers could adopt a more robust methodology, such as a randomised controlled trial, and incorporate further design elements, such as longitudinal follow-up. Providing more systematic evidence of the beneficial role of mindfulness for conservatoire music students as learners and performers may encourage greater provision of such opportunities in musical settings in the future.